Fifa world cup 2018 in Russia: implementation of digital technologies - Yu. V. Sinchuk; V. P. Zhuravel; B. E. Vlasov (Цифровая социология)
The FIFA World Cup 2018 (hereinafter – the World Cup 2018), held in Russia in summer of 2018, became a major world sports event and at the same time a major image and infrastructure project. The article reveals in detail the preparation and holding of the FIFA World Cup 2018, and also gives its general characteristics. It has been noted, that the international task of improving the image of the Russian Federation at the present stage, the easing of international tensions in the world was achieved only partially. The necessity to pay special attention to security issues has been identified and justified. The article also highlights in detail the innovative approaches of Russia to the World Cup 2018, namely the implementation of new digital technologies for security control. Based on the carried out study, recommendations on further use of sports infrastructure, attraction of youth in sports activities, in particular, promotion of football have been given, it has been offered to consider possibility of implementation of the use system of the passport of the fan in the realities of modern Russia.